Monitoring and Evaluation of Climate-Smart Agriculture Investments. Methodology and Approach - Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation for teams developing climate-smart agricutlure investment plans